Structural Analytic Synthetic Learning Method for Early Reading Ability - Damayanti, Anita; Suradika, Agus; Roshonah, Adiyati Fathu; Pujiati, Desti; Nur Aini, Aisyah; Rahmah, Silvia Fiqriyah (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
The Structural Analytic Synthetic (SAS) method is a learning method that begins with the introduction of complete sentence structures that build meaningful concepts in children. This research aimed to determine the effect of the SAS method on children's early reading abilities. This research uses a quantitative method with an experimental approach, using a pre-experimental one-group pretest and posttest design. Participants in this research were all early childhood children aged 6-7 years, totaling 32 children. Collection techniques include observation, interviews, and tests. The use of the SAS method in classroom learning has a positive influence, children's initial reading Ability when applying the SAS method in learning has a very big influence. The SAS method is an initial reading learning method that begins with presenting complete sentences which are then broken down into words into independent syllables and letters and combined again starting from letters into syllables, and words into complete sentences. Keywords: children aged 6-7 years, early reading ability, structural analytic-synthetic method References: Aro, M. (2017). Learning to read Finnish. In L. Verhoeven & C. Perfetti (Eds.), Learning to read across languages and writing systems (pp. 416–436). Cambridge: Cambridge University Press. Brodin, J., & Renblad, K. (2020). Improvement of preschool children’s speech and language skills. Early Child Development and Care, 190(14), 2205–2213. https://doi.org/10.1080/03004430.2018.1564917 Cain, K. (2016). Reading comprehension and difficulties: An overview. Perspectives on Language and Literacy, 42(2), 9–16. Dehaene, S., Cohen, L., Morais, J., & Kolinsky, R. (2015). Illiterate to literate: Behavioural and cerebral changes induced by reading acquisition. Nature Reviews Neuroscience, 16(4), 234–244. https://doi.org/10. 1038/nrn3924 Ediwarman, & Meliyawati. (2019). Kiat Membaca Dan Penerapannya. Yogyakarta: Deepublish. Emgusnadi. (2018). Metode Pembelajaran Sas Untuk Meningkatkan Keterampilan Membaca Siswa Kelas I Sd Negeri 021 Sitorajo Kari Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi. Jurnal Pajar (Pendidikan Dan Pengajaran), 659–655. Eklund, K., Torppa, M., Sulkunen, S., Niemi, P., & Ahonen, T. (2018). Early cognitive predictors of PISA Reading in children with and without family risk for dyslexia. Learning and Individual Differences, 64, 94–103. https://doi.org/10.1016/j.lindif.2018.04.012. Georgiou, G. K., Parrila, R., & Papadopoulos, T. C. (2008). Predictors of word decoding and reading fluency across languages varying in orthographic consistency. Journal of Educational Psychology, 100(3), 566–580. https://doi.org/10.1037/0022-0663.100.3.566. Ginting, M. B. (2020). Buku Ajar Bahasa Indonesia Sekolah Dasar Kelas Rendah. Klaten: Penerbit Lakeisha. Hasibuan, S. (2019). Penggunaan Metode Sas Dalam Peningkatan Kemampuan Membaca Permulaan Pada Siswa Kelas 1 Sdn 106162 Medan Estate. (Sej) School Education Journal, 9, 186. Hidayah, N., & Novita. (2016). Peningkatkan Kemampuan Membaca Permulaan Dengan Menggunakan Metode Struktural Analitik Sintetik (Sas) Mata Pelajaran Bahasa Indonesia Pada Peserta Didik Kelas Ii C Semester Ii Di Min 6 Bandar Lampung T.A 2015/2016. Jurnal Pendidikan Dan Pembelajaran Dasar, Volume 3, Nomor 1, 85-102. Landerl, K., Freudenthaler, H. H., Heene, M., De Jong, P. F., Desrochers, A., Manolitsis, G., ... Georgiou, G. K. (2019). Phonological awareness and rapid automatized naming as longitudinal predictors of reading in five alphabetic orthographies with varying degrees of consistency. Scientific Studies of Reading, 23(3), 220–234. https://doi.org/10.1080/ 10888438.2018.1510936 Manolitsis, G., Georgiou, G. K., & Parrila, R. (2011). Revisiting the home literacy model of reading development in an orthographically consistent language. Learning and Instruction, 21(4), 496–505. Musbikin, I. (2019). Penguatan Pendidikan Karakter (Ppk). Nusamedia. Mustadi, A., Sayekti, O. M., Rochmah, E. N., Zubaidah, E., Sugiarsih, S., & Schulze, K. M. (2022). Pancalis: Android-Based Learning Media for Early-Reading In New Normal. Cakrawala Pendidikan, 41(1), 71–82. Https://Doi.Org/10.21831/Cp.V41i1.45883 Perry, C., Zorzi, M., & Ziegler, J. C. (2019). Understanding dyslexia through personalized large-scale computational models. Psychological Science, 30(3), 386–395. https://doi.org/10.1177/0956797618823540 Pertiwi, P., & Sugiyanto. (2015). Efektivitas Permainan Konstruktiv Aktif Untuk Meningkatkan Kemampuan Membaca Siswa Kelas 2 Sd. Jurnal Psikologi Universitas Gajah Mada, 34, 151-163 Puolakanaho, A., Ahonen, T., Aro, M., Eklund, K., Leppänen, P. H. T., Poikkeus, A.-M., et al. (2007). Very early phonological and language skills: Estimating individual risk of reading disability. Journal of Child Psychology and Psychiatry, 48(9), 923–931. https://doi.org/10.1111/j.1469-7610.2007.01763.x. Rahayu, Tri. (2014). Perkembangan Kemampuan Membaca Siswa Berdasarkan Alat Evaluasi Membaca Berbasis Portofolio, Fpbs. Bandung: Universitas Pendidikan Indonesia Sabrina, A., & Laily, I. F. (2016). Perbandingan Kemampuan Membaca Permulaan Antara Siswa Kelas I Melalui Tk Dengan Tidak Melalui Tk Di Mi Pgm Kota Cirebon. Al-Ibtida, 332. Skeide, M. A., Kumar, U., Mishra, R. K., Tripathi, V. N., Guleria, A., Singh, J. P., ... Huettig, F. (2017). Learning to read alters cortico-subcortical cross-talk in the visual system of illiterates. Science Advances, 3(5), e1602612. https://doi.org/10.1126/sciadv.1602612 Sugiyono. (2017). Metode Penelitian Kombinasi: (Pendekatan kuantitatif, kualitatif dan R & D). Alfabeta. Sulistyawati, E. E. , & Sujarwo. (2016). Peningkatan Kemampuan Membaca Permulaan Melalui Media Video Compact Disc Pada Anak Usia 5-6 Tahun. Jurnal Pendidikan Dan Pemberdayaan Masyarakat, 3, 28–37. Tela, T., Yulian, V. N., & Budianingsih, Y. (2019). Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share (Tps) Terhadap Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa. Biormatika : Jurnal Ilmiah Fakultas Keguruan Dan Ilmu Pendidikan. Torppa, M., Eklund, K., van Bergen, E., & Lyytinen, H. (2015). Late-emerging and resolving dyslexia: A follow-up study from kindergarten to Grade 8. Journal of Abnormal Child Psychology, 43(7), 1389–1401. https://doi.org/10.1007/s10802-015-0003-1. Wathoni, L. M. (2020). Pendidikan Islam Dengan Menyikapi Kontroversi Belajar Membaca Pada Anak Usia Dini. Mataram: Sanabil. Yulsyofriend. (2013). Permainan Membaca Dan Menulis Anak Usia Dini. Padang : Sukabina Ziegler, J. C., Perry, C., & Zorzi, M. (2020). Learning to read and dyslexia: From theory to intervention through personalized computational models. Current Directions in Psychological Science, 29, 293–300. https://doi.org/10.1177/0963721420915873